Conference report: Academic conference “Perspektywy kształcenia nauczycieli języków specjalistycznych w Polsce” (Perspectives on educating LSP teachers in Poland), Institute of Applied Linguistics of Adam Mickiewicz University in Poznań, 20th October 2020 - KRAWIEC, MAREK (Glottodidactica, 2021)
Conference report: Academic conference “Perspektywy kształcenia nauczycieli języków specjalistycznych w Polsce” (Perspectives on educating LSP teachers in Poland), Institute of Applied Linguistics of Adam Mickiewicz University in Poznań, 20th October 2020.